Metabolic changes with the occurrence of atherosclerotic plaques and the effects of statins - Zhao, Lingmin; Ma, Di; Wang, LiJuan; Su, XingQi; Feng, LiangShu; Zhu, LiChong; Chen, Ying; Hao, YuLei; Wang, XinYu; Feng, JiaChun (Frontiers in Immunology, 2023)
Atherosclerosis is a common cardiovascular disease caused by the abnormal expression of multiple factors and genes influenced by both environmental and genetic factors. The primary manifestation of atherosclerosis is plaque formation, which occurs when inflammatory cells consume excess lipids, affecting their retention and modification within the arterial intima. This triggers endothelial cell (EC) activation, immune cell infiltration, vascular smooth muscle cell (VSMC) proliferation and migration, foam cell formation, lipid streaks, and fibrous plaque development. These processes can lead to vascular wall sclerosis, lumen stenosis, and thrombosis. Immune cells, ECs, and VSMCs in atherosclerotic plaques undergo significant metabolic changes and inflammatory responses. The interaction of cytokines and chemokines secreted by these cells leads to the onset, progression, and regression of atherosclerosis. The regulation of cell- or cytokine-based immune responses is a novel therapeutic approach for atherosclerosis. Statins are currently the primary pharmacological agents utilised for managing unstable plaques owing to their ability to enhance endothelial function, regulate VSMC proliferation and apoptosis by reducing cholesterol levels, and mitigate the expression and activity of inflammatory cytokines. In this review, we provide an overview of the metabolic changes associated with atherosclerosis, describe the effects of inflammatory responses on atherosclerotic plaques, and discuss the mechanisms through which statins contribute to plaque stabilisation. Additionally, we examine the role of statins in combination with other drugs in the management of atherosclerosis.